Association between the composite dietary antioxidant index and risk of endometriosis in women: a national population-based study - Yu, Yanmei; Sun, Jianan; Wang, Dandan; Xing, Miaomiao; Yang, Yanqi (Frontiers in Nutrition, 2025)
BackgroundComposite dietary antioxidant index (CDAI) has been found protective to women’s health. However, the association between CDAI level and the risk of endometriosis in women is unclear.MethodsA total of 4,153 women from the National Health and Nutrition Examination Survey (NHANES) 2001–2006 were included in this cross-sectional study. We evaluated the association between CDAI level and the risk of endometriosis using three logistic regression models and restricted cubic spline. Stratified and sensitivity analyses were also performed.ResultsLogistic regression analysis found that CDAI level was inversely associated with the development of endometriosis. The associated odds ratio (OR) for each SD increase in CDAI was 0.98 [95%CI: 0.96–0.99]. After dividing the CDAI level into four quartiles, we found that compared with the CDAI level in Q1 (−1.89, −1.79), the ORs [95%CI] associated with endometriosis in Q2 (−1.79, −0.69), Q3 (−0.69, 1.42) and Q4 (1.42, 47.92) were 0.94 [0.87, 1.03], 0.95 [0.88, 1.04] and 0.83 [0.77, 0.91], respectively, with p trend<0.001. Restricted cubic spline showed a negative dose–response relationship between CDAI level and endometriosis risk. In addition, the protective effect of CDAI on endometriosis was more obvious in women aged 30–39 years (OR = 0.83, 95% CI = 0.69–0.99), gave relatively more births (OR = 0.82, 95% CI = 071–0.93), lower family income (OR = 0.69, 95% CI = 0.54–0.88), Non-Hispanic Black (OR = 0.72, 95% CI = 0.58–0.89), less educated (OR = 0.69, 95% CI = 0.52–0.91), smoker (OR = 0.74, 95% CI = 0.61–0.89), alcohol drinker (OR = 0.86, 95% CI = 0.77–0.97), overweight or obese (OR = 0.76, 95% CI = 0.60–0.97), and hypertensive (OR = 0.72, 95% CI = 0.60–0.87).ConclusionOur findings may provide valuable insights into the primary prevention of endometriosis in women and further prospective studies are warranted.